2017
DOI: 10.1038/s41598-017-11367-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide RAD sequencing data provide unprecedented resolution of the phylogeny of temperate bamboos (Poaceae: Bambusoideae)

Abstract: The temperate bamboos (tribe Arundinarieae, Poaceae) are strongly supported as monophyly in recent molecular studies, but taxonomic delineation and phylogenetic relationships within the tribe lack resolution. Here, we sampled 39 species (36 temperate bamboos and 3 outgroups) for restriction-site associated DNA sequencing (RAD-seq) with an emphasis on Phyllostachys clade and related clades. Using the largest data matrix for the bamboos to date, we were able to infer phylogenetic relationships with unparalleled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
47
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 60 publications
11
47
2
Order By: Relevance
“…2, 3), demonstrating the power of RAD-seq data that contain thousands of loci across the genome in phylogenetic studies. Much better-resolved and more strongly supported phylogenies from analyses of RAD-seq data, compared with previous phylogenies based on only a few genes, have also been reported in other studies (Wang et al, 2017;Deng et al, 2018;Du et al, 2020). Although RAD-seq data were generally considered appropriate for phylogenomic studies of young lineages of recent divergence due to concerns regarding allelic dropout, this study and others (Leaché & Oaks, 2017;Du et al, 2020;Zhou et al, 2020) have shown that RAD-seq data generated from careful preparation of DNA libraries are also valuable for phylogenomic studies of lineages with divergence dated back to the late Cretaceous or early Paleogene.…”
Section: Discussionsupporting
confidence: 79%
“…2, 3), demonstrating the power of RAD-seq data that contain thousands of loci across the genome in phylogenetic studies. Much better-resolved and more strongly supported phylogenies from analyses of RAD-seq data, compared with previous phylogenies based on only a few genes, have also been reported in other studies (Wang et al, 2017;Deng et al, 2018;Du et al, 2020). Although RAD-seq data were generally considered appropriate for phylogenomic studies of young lineages of recent divergence due to concerns regarding allelic dropout, this study and others (Leaché & Oaks, 2017;Du et al, 2020;Zhou et al, 2020) have shown that RAD-seq data generated from careful preparation of DNA libraries are also valuable for phylogenomic studies of lineages with divergence dated back to the late Cretaceous or early Paleogene.…”
Section: Discussionsupporting
confidence: 79%
“…At the genus level, the nuclear phylogeny of Ficus is more in accordance with the classic subdivision (Bruun‐Lund & al., 2017). This phenomenon was also reported in Cyperaceae, Rosaceae, and Poaceae (Massatti & al., 2016; Xiang & al., 2016; Wang & al., 2017). These observations imply that the nuclear phylogeny of Ficus may be a suitable model for the investigation of evolutionary history.…”
Section: Discussionmentioning
confidence: 99%
“…These results implied that the nuclear genome and the plastid genome may have different evolutionary trajectories (Zhang et al 2012;Yang et al 2013). The most recent study based on phylogenetic analyses with RAD-seq data identified eight major lineages in Arundinarieae with strong support, which conflicts with earlier studies (Wang et al 2017).…”
Section: Introductionmentioning
confidence: 59%